Autoanti-idiotypes exhibit mimicry of myocyte antigens in virus-induced myocarditis. - Paque, R E (1991)
Mice infected with coxsackievirus B develop immunologically mediated inflammatory myocarditis in heart tissue that results in the development of autoantibodies with multiple idiotypes. The specificity and temporal development of autoantibodies produced during coxsackievirus B3 infection were assessed. Antiviral idiotypes and anti-idiotypic antibodies against coxsackievirus B3 idiotypes were detected and quantitated over 21- and 42-day periods, respectively. Both polyclonal and monoclonal anti-idiotypes exhibited greater but nonspecific binding to heart, liver, kidney, and spleen cells from virus-exposed animals and normal tissue. Binding of anti-idiotypes was also demonstrated to myosin and to solubilized heart-associated antigens but not to virus. Western immunoblot analysis revealed that monoclonal and polyclonal anti-idiotypes selectively bound to hypertonic, salt-extracted, solubilized proteins of myocyte extracts of virus-exposed animals.